2019
DOI: 10.21203/rs.2.107/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arthritis prevention in the pre-clinical phase of RA with abatacept (the APIPPRA study): a multi-centre, randomised, double blind, parallel group placebo-controlled clinical trial Protocol

Abstract: Trial design: We present a study protocol for a multi-centre, randomised, double blind, parallel group, placebo-controlled trial that seeks to test the feasibility, acceptability and effectiveness of a 52-week period of treatment with the first-in-class costimulatory blocker abatacept for preventing or delaying the onset of inflammatory arthritis. Methods: The study aimed to recruit 206 male or female subjects from the secondary care hospital setting across the UK and the Netherlands. Participants aged 18 or o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Environmental factors including lifestyle are important in RA development and lifestyle intervention may delay or prevent RA onset [5][6][7]. In addition, several placebo controlled clinical trials in individuals at increased risk of RA have been performed or are ongoing [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors including lifestyle are important in RA development and lifestyle intervention may delay or prevent RA onset [5][6][7]. In addition, several placebo controlled clinical trials in individuals at increased risk of RA have been performed or are ongoing [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a trial suggested the possibility that abatacept may alter the progression of RA at a very early stage, although it was not found to be statistically signi cant [38]. To con rm this, a larger randomized trial is in process [39].…”
Section: Discussionmentioning
confidence: 99%
“…Such patients, in the earliest phases of clinical disease, are often difficult to assess and the clinical findings can be subtle. Clinical trials investigating arthritis prevention in individuals at-risk of RA are increasingly stipulating US confirmation of clinical synovitis for this reason [18]. Despite the several advantages described above, there are some important considerations which must be borne in mind for the optimum use of US in individuals at-risk of RA without clinical synovitis.…”
Section: The Utility Of Ultrasound In Managing Individuals At-risk Ofmentioning
confidence: 99%